Biossegurança e a negligência em laboratório de prótese dentária, à luz da NR 32 - Rezende, Aparecida Elaine Figueiredo (2022)
The objective of this research was to investigate the behaviour of Dental Prosthesis Technicians and Dental Prosthesis Assistants. This study is related to biosafety and has the purpose to question whether, in the light of NR 32, there is misinformation and/or negligence with the health of professionals who work in dental laboratories of dental prosthesis in the city of Uberlândia-MG. In addition this study also has the purpose to investigate the reality in the routine of the work activities of the TPD/APD identifying and evaluating the effective application of NR 32, the occupational risks having the main focus the biological risks and the difficulties in the disinfection and sterilization procedures of materials, prosthetic parts and surfaces in laboratories, and, consequently, the high rates of cross-infection. The research was done by a questionnaire application to professionals whose data collection was gathered in the year 2021 based on integrative review to determine the current knowledge on the proposed topic, whose studies can bring valuable subsidies and improvements in the implementation of biosecurity measures to the dental prosthesis area. Finally, this study evaluated the compliance with the rules and its importance, helping biosafety applicability measures in the performance of daily basis work activities seeking to preserve the health and safety of professionals regarding the reality of these work environments. It was found that the professionals working in the dental prosthesis laboratories in the city of Uberlândia-MG meet the minimum requirements determined by NR 32 necessary for the execution of a safe work, which follow the guidelines contained in the regulatory standard. For this reason, we can conclude thar there is no negligence. The results shows that is unnecessary to propose a product (protocol) that deals with the importance of biosecurity measures. However, the elaboration of a specific standard by Organs competent bodies will bring greater interest to TPD and APD, in the performance of activities in the routine of work in dental laboratories. In order to maintain the level of information on biosafety desirable to appropriate antisepsis practices and conduct in contact with health-aggressive agents present in the work environment by using the through the application of NR 32, It is recommended that the Regional Council of Dentistry of the State of Minas Gerais - CRO/MG, as a professional class entity in the field of dentistry, remains the main link between the TPD and APD.